Upgrading sensible-heat storage with a thermochemical storage section operated at variable pressure: An effective way toward active control of the heat-transfer fluid outflow temperature. (15th June 2017) - Ströhle, S.; Haselbacher, A.; Jovanovic, Z.R.; Steinfeld, A.
Graphical abstract: Highlights: A novel combined sensible-heat/thermochemical storage concept is proposed. The outflow temperature of the heat-transfer fluid can be actively controlled. The energy/exergy efficiencies are compared to sensible-heat storage. Abstract: This article introduces a novel thermal-energy storage concept that allows the outflow temperature of the heat-transfer fluid to be controlled during discharging. The concept is based on placing a thermochemical-storage section on top of a sensible thermal-energy storage section. The thermochemical-storage section comprises tubes that house gaseous and solid reactants undergoing reversible endo/exothermic cycling. Because the reactants are physically separated from the heat-transfer fluid, the reaction pressure can be independently adjusted using a compressor. As a result, the equilibrium reaction temperature can be tuned to reach the rate and temperature of the exothermic reaction that allow the heat-transfer fluid passing the tubes to be heated to a desired temperature during discharging. Transient simulations of such a combined sensible/thermochemical thermal-energy storage confirm that during discharging the heat-transfer fluid can be heated to a constant outflow temperature that is equal to or higher than the inflow temperature during charging. The calculated cycle efficiency of the combined storage accounts for the parasitic losses introduced by the reaction pressure swing and is compared to the cycle efficiency of a sensible storage operating under equal inflow conditions.